A Vector-Based Motion Retargeting Approach for Exoskeletons with Shoulder Girdle Mechanism - Jiajia Wang; Shuo Pei; Junlong Guo; Mingsong Bao; Yufeng Yao (Biomimetics)
Shoulder girdle plays a dominant role in coordinating the natural movements of the upper arm. Inverse kinematics, optimization, and data-driven approaches are usually used to conduct motion retargeting. However, these methods do not consider shoulder girdle movement. When the kinematic structure of human and that of exoskeletons share a similar joint configuration, analytical motion retargeting methods can be used for exoskeletons with shoulder girdle mechanism. This paper proposes a vector-based analytical motion retargeting approach for exoskeletons with shoulder girdle mechanism. The approach maps the vectors of the upper limb segments to the joint space using vector-based methods. Simulation results using four different motion descriptions confirm the method’s accuracy and efficiency.